DEPRESSIVE MENTAL DISORDER AS A RISK FACTOR AND AUTOCIDITY EXECUTION - de Paula Ferreira, Larissa; Veggi Moreira, Raquel; Lacerda Tinoco Boechat Cabral, Hildeliza; Henrique Medeiros de Souza, Carlos (LINKSCIENCEPLACE, 2026)
Our postmodern social body brings with it more and more occupations and preoccupations. In view of this, the World Health Organization has in no way recorded as many cases of anxiety, depression, and other psychosomatic disorders as these days. The objective of this work is to examine the current progressive context of depressive compulsions and, consequently, of suicidal practices. This approach is justified by the current attention and discussion on the subject, since such circumstances are understood as contemporary problems that, under the current legal order of the country, are subject to the principle of human dignity. In the use of qualitative methodology, it is established in the analysis of works and scientific productions of theorists in the subject, as well as in current legal guidelines.